2017
DOI: 10.5751/ace-00974-120114
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous recording units in avian ecological research: current use and future applications

Abstract: ABSTRACT. Acoustic surveys are a widely used sampling tool in ecological research and monitoring. They are used to monitor populations and ecosystems and to study various aspects of animal behavior. Autonomous recording units (ARUs) can record sound in most environments and are increasingly used by researchers to conduct acoustic surveys for birds. In this review, we summarize the use of ARUs in avian ecological research and synthesize current knowledge of the benefits and drawbacks of this technology. ARUs en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
265
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 245 publications
(267 citation statements)
references
References 66 publications
(96 reference statements)
2
265
0
Order By: Relevance
“…This can result in low detectability and misidentifications. Reinterpretation of ARU-based data provides an opportunity to correct errors, verify unknowns, and reduce inter-and intraobserver errors (Rempel et al 2005, Campbell and Francis 2011, Shonfield and Bayne 2017. Another promising contribution of ARUs to the BBS is the possibility to increase data quantity and quality by sampling at different time periods with no additional added field effort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can result in low detectability and misidentifications. Reinterpretation of ARU-based data provides an opportunity to correct errors, verify unknowns, and reduce inter-and intraobserver errors (Rempel et al 2005, Campbell and Francis 2011, Shonfield and Bayne 2017. Another promising contribution of ARUs to the BBS is the possibility to increase data quantity and quality by sampling at different time periods with no additional added field effort.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to assess whether employing ARUs would introduce systematic biases in species richness and speciesspecific abundance indices derived by on-road ARU BBS and forest-edge ARU BBS surveys relative to human BBS surveys, i.e., recordings of the same 3-minute period. Some studies have shown differences in detectability between human-and recording-based surveys, whereas others have not (e.g., Hutto and Stutzman 2009, Campbell and Francis 2011, Venier et al 2012, Shonfield and Bayne 2017. However, documenting the relative importance of survey type (human vs. ARU-based surveys) and sampling location (on-road vs. forest edge) on bird counts is key to understanding and thereby standardizing differences between human and ARUbased roadside monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could have achieved a similar increase in precision through additional point counts at each site, but it would have been challenging for us to access each of our survey sites on 3 consecutive mornings. Others have noted the advantages of automated recorders, including limited availability of expert point count observers, synchronization of survey times among sites, and a verifiable record of bird detections (Hobson et al 2002, Rempel et al 2005, Shonfield and Bayne 2017. In our case, we used both methods, which further increased precision by allowing us to sample over a greater diversity of times of the morning.…”
Section: Discussionmentioning
confidence: 99%
“…Vocalizations are also the primary means by which observers in the field identify birds using standard point counts (Ralph et al 1995) or automated recorders (Shonfield and Bayne 2017). Both techniques have been applied to efficiently survey birds across large geographic areas (McGrann et al 2014, Furnas andCallas 2015).…”
Section: Introductionmentioning
confidence: 99%